QTL for Yield Traits and Their Association with Functional Genes in Response to Phosphorus Deficiency in Brassica napus - Shi, Taoxiong (Public Library of Science, 2013)

(untitled)
BACKGROUND: Oilseed rape (Brassica napus L.) is one of the most important oil crops. A primary limitation to the cultivation of this crop is the lack of available phosphorus (P) in soils. To elucidate the genetic control of P deficiency tolerance in Brassica napus, quantitative trait locus (QTL) for seed yield and yield related-traits in response to P deficiency were identified using a double haploid mapping population (TN DH) derived from a cross between a P-efficient cultivar, Ningyou 7 and a P-inefficient cultivar, Tapidor. RESULTS: Three field trials were conducted to determine seed yield (SY), plant height (PH), number of primary branches (BN), height to the first primary branch (FBH), relative first primary branch height (RBH), pod number per plant (PN), seed number per pod (SN) and seed weight of 1,000 seeds (SW) in 188 lines of TN DH population exposed to low P (LP) and optimal P (OP) conditions. P deficiency decreased PH, BN, SN, PN and SY, and increased FBH and RBH with no effect on SW. Three reproducible LP-specific QTL regions were identified on chromosomes A2, A3 and A5 that controlled SN, PN and SW respectively. In addition, six reproducible constitutive regions were also mapped with two each for SY-LP on A2, and FBH-LP on C6 and one each for PH-LP and SW-LP on A3. About 30 markers derived from 19 orthologous genes involved in Arabidopsis P homeostasis were mapped on 24 QTL regions by comparative mapping between Arabidopsis and Brassica napus. Among these genes, GPT1, MGD2 and SIZ1 were associated with two major loci regulating SY-LP and other yield-related traits on A2 between 77.1 and 95.0 cM. CONCLUSION: The stable QTLs detected under LP conditions and their candidate genes may provide useful information for marker-assisted selection in breeding high-yield B. napus varieties with improved P efficiency.